Optimising platelet secretomes to deliver robust tissue‐specific regeneration. (11th November 2019) - Scully, David; Sfyri, Peggy; Wilkinson, Holly N.; Acebes‐Huerta, Andrea; Verpoorten, Sandrine; Muñoz‐Turrillas, María Carmen; Parnell, Andrew; Patel, Ketan; Hardman, Matthew J.; Gutiérrez, Laura; Matsakas, Antonios
Abstract: Promoting cell proliferation is the cornerstone of most tissue regeneration therapies. As platelet‐based applications promote cell division and can be customised for tissue‐specific efficacy, this makes them strong candidates for developing novel regenerative therapies. Therefore, the aim of this study was to determine if platelet releasate could be optimised to promote cellular proliferation and differentiation of specific tissues. Growth factors in platelet releasate were profiled for physiological and supraphysiological platelet concentrations. We analysed the effect of physiological and supraphysiological releasate on C2C12 skeletal myoblasts, H9C2 rat cardiomyocytes, human dermal fibroblasts (HDF), HaCaT keratinocytes, and chondrocytes. Cellular proliferation and differentiation were assessed through proliferation assays, mRNA, and protein expression. We show that supraphysiological releasate is not simply a concentrated version of physiological releasate. Physiological releasate promoted C2C12, HDF, and chondrocyte proliferation with no effect on H9C2 or HaCaT cells. Supraphysiological releasate induced stronger proliferation in C2C12 and HDF cells compared with physiological releasate. Importantly, supraphysiological releasate induced proliferation of H9C2 cells. The proliferative effects of skeletal and cardiac muscle cells were in part driven by vascular endothelial growth factor alpha. Furthermore, supraphysiological releasate induced differentiation of H9C2 and C2C12, HDF, and keratinocytes. This study provides insights into the ability of releasate to promote muscle, heart, skin, and cartilage cell proliferation and differentiation and highlights the importance of optimising releasate composition for tissue‐specific regeneration.